RESPON PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays-saccharata Sturt.) PADA PEMBERIAN PUPUK TERPADU DI KOTA YOGYAKARTA - Sholikhah Nurlaila; Maria Theresia, Darini; Sri, Widata (JURNAL ILMIAH AGROUST, 2023)
This study aims to determine the source of organic fertilizer and the correct dose of NPK fertilizer that can increase the growth and yield of sweet corn, and to determine the interaction between the source of organic fertilizer and dose of NPK fertilizer on the growth and yield of sweet corn. This research was conducted in June – December 2022, located in Giwangan, Yogyakarta. This research was arranged using RCBD with 2 factors. First factor is the source of organic fertilizer consisting of chicken manure, cow manure, and household waste compost. Second factor was the dose of NPK fertilizer which consisted of 100 kg/ha, 150 kg/ha, and 200 kg/ha. The variables obeserved include growth variables consisting of plant height, number of leaves, leaf area, plant fresh weight, plant dry weight, and chlorophyll content and yield variables consisting of plant fresh weight, plant dry weight, cob weight, cob diameter, yield per hectare, number of rows of seeds on the cob, and fruit sweetness level. Data analysis used was a 5% level of variance followed by a 5% DMRT test. The result showed that there was no interaction with all variables, except for the level of sweetness of the fruit. Organic fertilizer sources have no effect on all variables. NPK fertilizer dose treatment didn’t affect all variables. The combination of treatments with organic fertilizer sources (chicken manure, cow manure, compost) and NPK fertilizer doses (100, 150, 200) kg/hashowed no effect on the control of growth variables, but had an effect on yield variables. Keywords: source of organic fertilizer, dose of NPK fertilizer, growth and yield, sweet corn.